PELAKSANAAN PERKAWINAN DENGAN WALI HAKIM DI KEPENGHULUAN SUAK TEMENGGUNG KECAMATAN PEKAITAN KABUPATEN ROKAN HILIRDITINJAU DARI HUKUM ISLAM - Ningrum Susilawati; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The law of marriage in Religion of Islam has a very important provision, therefore the rules concerning marriage are arranged and explained clearly and in detail. Islamic Marriage Law is basically not only regulate the practice of marriage but also regulate all issues closely related to marriage. The marriage procedure in Indonesia is categorized differently from one to the other because in Indonesia it recognizes the existence of various religions and beliefs, which are different.Marriage is a sacred part of life, because it must pay attention to norms and rules of life in society. According to the provisions of Article 2 paragraph (1) of Law Number 1 Year 1974 that a marriage is considered valid if done according to religion and belief and recorded by authorized officials. In Indonesia, marriage regulations For Muslims are set out in detail in the Compilation of Islamic Law on get alon and the terms of marriage that must be met and between one with others should not be left behind. One of them is about the guardian in marriage. If the guardian of the nasab is still in place and there is no obstacle whatsoever then he must marry the bride in order of position of guardianship arranged in Articles 21,22 and 23 KHI.The problems that the authors make the basis of the research is How the implementation of marriage with the judge's guardian in Kepenghuluan Suak Temenggung, What factors cause the implementation of marriage with the guardian judges in Kepenghuluan Suak Temenggung and what is the result of marriage with judges in Kepenghuluan Suak Temenggung Pekaitan District Rokan Hilir Regency reviewed of Islamic law. The research method used is descriptive sociological juridical. Source of data used in this research that comes from primary and secondary data. Data analysis uses qualitative data analysis and draw conclusions with deductive methods. The results of this study indicate that: first, marriage is done with the judge's guardian at the time the wali nasab is in place and without any obstacle to marrying the bride. Second, the factors causing the marriage with judges are due to customary factors, inability to pronounce lafaz marriage contract, religious factors, educational factors, and lack of socialization from the relevant agencies. As a result of the implementation of this marriage is the unfulfillance of the get alon and marriage conditions in accordance with Articles 21, 22 and 23 KHI, not achieving Article 2 of the UUP, marriage can be canceled and become a habit in the community kepenghuluan Suak Temenggung. According to the authors, people who have the right of guardianship in a marriage exercise should be better able and understand in using the right of guardianship because the role of the guardian determines the validity of a marriage implementation.Keywords: Implementation - Marriage - guardian of judges - Kepenghuluan Suak Temenggung.